Quality of castor bean seeds (Ricinus communis l.) affected by raceme and fruit position during storage - Machado, Carla Gomes; Martins, Cibele Chalita; Cruz, Simério Carlos Silva; Nakagawa, João; Pereira, Francisco Rafael da Silva (Semina: Ciências Agrárias, 2010)
The present research had as objective to evaluate the influence of raceme and fruit position on physiological quality of castor bean seeds (Ricinus communis L.) during storage of cultivar AL Guarany 2002. The treatments were: position of the raceme in plants (primary, secondary and tertiary) and position of fruit in racemes (low, medium and high). After fruit extraction, seeds were stored under environmental conditions for twelve months. The experimental design used was the completely randomized in a split-plot arrangement. Main plots consisted of the interaction raceme x fruit position and subplots were the storage time. Physiological quality was evaluated quarterly through tests of moisture content, germination and vigor (first count, accelerated aging, seedling length and seedling dry matter). Neither the position of racemes in the plant nor fruit in racemes does not affect germination of castor bean seeds. Dormancy of castor bean seeds decreases during storage, but also increases percentage of abnormal seedlings, seedling dry matter and root, hypocotyl and seedling total length.